Volatile organic compounds and their contribution to ground-level ozone formation in a tropical urban environment - Zulkifli, Mohd Faizul Hilmi; Hawari, Nor Syamimi Sufiera Limi; Latif, Mohd Talib; Abd Hamid, Haris Hafizal; Ahmad Mohtar, Anis Asma; Wan Idris, Wan Mohd Razi; Mustaffa, Nur Ili Hamizah; Liew, Juneng (Elsevier, 2022)
This study aims to determine the trends of volatile organic compound (VOC) concentrations and their potential contribution to O3 formation. The hourly data (August 2017 to July 2018) for 29 VOCs were obtained from three Malaysian Department of Environment continuous air quality monitoring stations with different urban backgrounds (Shah Alam, Cheras, Seremban). The Ozone Formation Potential (OFP) was calculated based on the individual Maximum Incremental Reactivity (MIR) and VOC concentrations. The results showed that the highest mean total VOC concentrations were recorded at Cheras (148 ± 123 μg m−3), within the Kuala Lumpur urban environment, followed by Shah Alam (124 ± 116 μg m−3) and Seremban (86.4 ± 89.2 μg m−3). VOCs such as n-butane, ethene, ethane and toluene were reported to be the most abundant species at all the selected stations, with overall mean concentrations of 16.6 ± 11.9 μg m−3, 12.1 ± 13.3 μg m−3, 10.8 ± 11.9 μg m−3 and 9.67 ± 9.00 μg m−3, respectively. Alkenes (51.3–59.1%) and aromatic hydrocarbons (26.4–33.5%) have been identified as the major contributors to O3 formation in the study areas based on the overall VOC measurements. Relative humidity was found to influence the concentrations of VOCs more than other meteorological parameters. Overall, this study will contribute to further understanding of the distribution of VOCs and their contribution to O3 formation, particularly in the tropical urban environment.